Legal education and land mediation as an effort to build legal certainty on border land in Dembe I Village - Bakung, Dolot Alhasni; Hadju, Zainal Abdul Aziz; Amrain, Fitran; Piyo, Sofyan; Elfikri, Nurul Fazri; Daud, Akbar Hidayatullah; Kadir, Muhamad Khairun Kurniawan (Society : Jurnal Pengabdian Masyarakat, 2026)
Border Land Management in coastal areas often presents juridical and social problems, including in Dembe I Village, Gorontalo City. Communities in this region face uncertainty about the legal status of the boundary land they occupy, although some have pocketed title certificates. The lack of legal understanding, the absence of village mediation institutions, and overlapping land administration add to the complexity of the problem. The thematic real work lecture (KKN) Program Phase II of Gorontalo State University was implemented to respond to these problems through a participatory and collaborative approach. The methods taken include legal counseling with the National Land Agency and the Faculty of law, citizen dialogue forums, participatory mapping, and the preparation of operational standards for land mediation procedures. The results of the activity showed an increase in Community Legal Literacy, the birth of critical awareness about the differences in formal rights and functions of space, as well as the drafting of mediation SOP documents as a local instrument for non-litigation dispute resolution. The conclusion of this activity confirms that the law can be presented in a communicative way to bridge the interests of the state in maintaining protected areas with the rights of communities in maintaining living space. This finding also implies that the model of service based on participatory legal education can be replicated in other coastal areas facing similar problems